2021
DOI: 10.1177/1938640020987741
|View full text |Cite
|
Sign up to set email alerts
|

Complications Following Total Ankle Arthroplasty Versus Ankle Arthrodesis for Primary Ankle Osteoarthritis

Abstract: Introduction There are minimal data comparing complications between ankle arthrodesis (AA) versus total ankle arthroplasty (TAR) for operative management of primary osteoarthritis (OA). This study aimed to compare outcomes following AA versus TAR for primary ankle OA using a large patient database. Methods Patients who received AA or TAR for primary ankle OA from 2010 to 2019 were queried from PearlDiver. Rates of common joint complications were compared at 90 days, 1 year, and 2 years postoperatively using mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 35 publications
0
7
0
1
Order By: Relevance
“…23 This may explain why subtalar joint OA progression is typically not observed in the majority of patients following TAR, with lower rates of adjacent joint complications. 14,35 Collectively, we view these biomechanical findings as being a favorable outcome of TAR in this patient group. We did, however, observe increased variability in the implanted tibiotalar internal/external rotation kinematics in the TAR limb, which we posit is due to the imprecision of positioning the talar implant in the axial plane for this specific Zimmer TAR implant.…”
Section: Discussionmentioning
confidence: 67%
“…23 This may explain why subtalar joint OA progression is typically not observed in the majority of patients following TAR, with lower rates of adjacent joint complications. 14,35 Collectively, we view these biomechanical findings as being a favorable outcome of TAR in this patient group. We did, however, observe increased variability in the implanted tibiotalar internal/external rotation kinematics in the TAR limb, which we posit is due to the imprecision of positioning the talar implant in the axial plane for this specific Zimmer TAR implant.…”
Section: Discussionmentioning
confidence: 67%
“…One challenge in comparing TAR and AA is that they have different advantages and types of complications 29 . TAR has the benefits of improved gait and protection of adjacent joints but may lead to implant loosening, polyethylene breakage, and persistent pain 3 , 4 , 6 , 8 .…”
Section: Discussionmentioning
confidence: 99%
“…We had a short follow-up of 2 years, while other studies have indicated that the revision rates of TAR are twice that of AA after 5 years 23 . Many surgical complications after TAR, such as loosening or breakage of the plastic insert, occur beyond 2 years 6 , 25 , 30 , while many complications following AA, such as wound problems, infection, and nonunion, occur within the first 2 years 29 , 31 . Additional studies with follow-up beyond 5 years are needed to advance our understanding of the benefits and limitations of TAR and AA 21 , 30 .…”
Section: Discussionmentioning
confidence: 99%
“…Due to residual mobility, OA of adjacent joints should in theory occur less often after TAA than after ankle arthrodesis [11,12]. However, there is a lack of studies directly comparing OA of adjacent joints after TAA and ankle arthrodesis, such as in a prospective randomized controlled trial setting [13][14][15][16]. Additionally, different rates of OA of adjacent joints after ankle arthrodesis have been reported in the literature [41].…”
Section: Discussionmentioning
confidence: 99%
“…The intended advantages of TAA are good residual mobility and thus improved function compared to arthrodesis [11,12]. In addition, an improved mobility of the ankle joint is intended to reduce the risk of subsequent OA in adjacent joints [11][12][13][14][15][16]. Due to its inferior survival rates compared to hip and knee replacement, TAA was mainly recommended for older and less active patients in the past [17][18][19].…”
Section: Introductionmentioning
confidence: 99%